A Robustand Dynamic Fault Detectionand Classficationof Semi-Conductorsusing Logistic Regression - et. al., Dr. K. Mohan Prasad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the semiconductor industry, the singular goal for automatic graphical assessment is to detect and categorize fabrication defects exploiting advanced image processing practices. The manufacturer main aim to detect the patterns at the quickest feasible recognition of defect models accepts quality management and computerization of production supply chains, companies benefit from a boosted yield and lowered production costs. Because conventional image processing systems are constrained in their capability to detect innovative defect models, and artificial intelligence methodology every so often involve a incredible amount of computational determination, this research presents a innovative deep neural network-based hybrid method.